MOVE EASY (CIPEEX, 2025)
Move Easy is a platform that facilitates the scheduling of transportation services, benefiting both clients and freelance hauliers. Its main objective is to optimize the scheduling process and help hauliers increase their production, promoting their economic development. In Brazil, where road transportation is the main means of transporting cargo, Move Easy stands out by seeking to fill the gaps in this business model. The way the platform works is centered on customers requesting services, which is its main functionality. In addition, Move Easy provides a communication channel between customers and hauliers via an integrated chat, keeping the personal data of both protected. Customers can also search for carriers in their region based on criteria such as vehicle type and size, as well as reviews of the service providers. This facilitates the efficient choice of the most suitable service and encourages carriers to maintain a good level of service, thanks to the feedback system. The creation of Move Easy was motivated by the realization that the road transport market still faces challenges, despite its relevance in Brazil. The platform seeks to solve these problems by offering a secure and efficient environment for transactions between customers and hauliers. The main features include integrated communication and the possibility of personalized searches for service providers, using criteria such as vehicle type and feedback from previous users. All of this aims to speed up the scheduling process, guarantee the safety of those involved and contribute to the growth of the sector. Move Easy's differential lies in its ability to meet the needs of both sides of the transaction. For customers, the platform offers a quick and practical way of finding the ideal transportation service. For hauliers, it increases visibility in the market and offers the opportunity to win new customers, as well as allowing them to expand their production volume. The feedback system is a fundamental part of this dynamic, encouraging hauliers to maintain a high standard of quality. Move Easy was validated through benchmarking, in which existing solutions were compared with the platform's proposal. This analysis revealed opportunities for improvement, especially in terms of communication between clients and hauliers, which led to the implementation of secure integration. The benchmarking also reinforced that Move Easy fills important gaps in the market, offering a safe and efficient service that has the potential to positively impact both users and the road transport sector as a whole. With its set of features and focus on efficiency, security and transparency, Move Easy presents itself as an innovative solution that promises to contribute to the growth of the road transport sector.
Keywords: transportation; scheduling; hauliers